Factors associated with bleeding after endoscopic variceal ligation in children. Issue 10 (20th August 2021) - Yokoyama, Shinya; Ishizu, Yoji; Ishigami, Masatoshi; Honda, Takashi; Kuzuya, Teiji; Ito, Takanori; Hinoki, Akinari; Sumida, Wataru; Shirota, Chiyoe; Tainaka, Takahisa; Makita, Satoshi; Yokota, Kazuki; et al.
Abstract: Background: Endoscopic variceal ligation (EVL) is a widely accepted treatment for esophagogastric varices in patients with portal hypertension (PHT). It is used for urgent treatment and prophylactic treatment of esophagogastric varices in pediatric as well as adult patients. However, major life‐threatening adverse events such as early rebleeding can occur. Although early rebleeding after EVL among children and adolescents has been reported, the risk factors remain obscure. This study evaluated the risk factors for early rebleeding after EVL in children and adolescents. Methods: The subjects were children and adolescents (<18 years) with PHT who underwent EVL for esophagogastric varices. Early rebleeding was defined as hematemesis, active bleeding, or blood retention in the stomach, confirmed by esophagogastroduodenoscopy from 2 h to 5 days after EVL. Results: A total of 50 EVL sessions on 22 patients were eligible for this study. There were four episodes of early rebleeding. No other major adverse event has occurred. Multivariate analysis showed that EVL implemented at cardiac varices just below the esophagogastric junction (EGJ), within 5 mm from the EGJ, is the independent factor for a higher risk of early rebleeding: odds ratio 18.2 (95% confidence interval: 1.40–237.0), P = 0.02. Conclusions: Children and adolescents who undergo EVL for cardiac varices just below the EGJ have a higher risk of early rebleeding than those who do not.